Chemical Screening of Some Himalayan Bryophytes - Sharma, Seema; Bisht, Manisha; Tiwari, S.D.; Mathela, C.S. (Asian Journal of Chemistry, 2010)
Eight bryophyte species collected from Kumaon (North-WesternHimalayas) nave been screened for their chemical constitutions. Thepresent communication reports the detection of terpenoids (mono-sesqui- and tri-) steroids, glycosides and flavonoids present in them.Alkaloids were not noticed in any of the material investigated. Thewide variety of terpenoids and flavonoids offer considerable scopefor the use of these plants. These chemical markers can be used inchemosystematics and biosynthetic studies.